Environmental educational potentials on school grounds in Budapest - Jákli, Eszter (Acta Geographica Debrecina Landscape & Environment series, 2018)
As nature and greenspaces in urban areas are agreed to enhance children’s appreciation towards nature and so the purposes of environmental education, it is of high importance to create spaces in and around schools that allow students to connect to nature on a daily basis. The aim of the study was to analyse functions and other components supporting environmental education appear in the open spaces of school grounds in Budapest, and to understand the main characteristics of school grounds with the highest potential in environmental education. The study points out that the presence of environmental educational functions often depends on the size, urban context and location of the school grounds, however the curriculum of the school does not necessarily influence its open spaces, while the presence of motivated and engaged teachers does. The study reveals environmental educational functions do exist in school grounds of primary schools in Budapest, however they play only secondary role behind active movement and play functions. The schools with the best potentials in environmental education are without doubt the ones situated on large plots in the suburban zone, mostly with a high proportion of green spaces in and around the school grounds.